Implementation Implementing JURASIC-Based Academic Supervision at SDN 1 Cilumber, West Bandung Regency - Kartini Nurhidayah; Diding Nurdin; Nugraha Suharto; Taufani C Kurniatun; Nurdin (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
Academic supervision is an important strategy for improving instructional quality and teacher professionalism in elementary schools. However, supervision practices often remain administrative and provide limited opportunities for reflective learning and professional growth. This study aimed to analyse the implementation of JURASIC-based academic supervision through reflective journaling and dialogic coaching at SDN 1 Cilumber, West Bandung Regency. A qualitative approach with an intrinsic case study design was employed. Participants included the principal and teachers involved in the JURASIC supervision program. Data were collected through in-depth interviews, classroom observations, reflective journals, and supervision documents, and were analysed using data reduction, data display, and conclusion drawing techniques, supported by source and method triangulation. The findings revealed that JURASIC-based supervision enhanced teachers’ reflective awareness, pedagogical competence, instructional planning, and classroom practices. Reflective journaling encouraged teachers to critically evaluate their teaching experiences and identify improvement strategies, while dialogic coaching facilitated constructive feedback, reflective dialogue, and collaborative problem-solving. In addition, the program contributed to the development of a collaborative professional learning culture within the school. Several challenges were identified, including limited supervision time, differences in teachers’ reflective writing abilities, and the need for consistent follow-up activities. The study concludes that integrating reflective journaling and coaching into academic supervision provides a contextual, reflective, and collaborative approach to strengthening teacher professionalism. Therefore, schools are encouraged to institutionalise reflective and coaching-based supervision as part of sustainable professional development programs